Wordarrows: The performative power of language in N. Scott Momaday's non-fiction work - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
Author/s Anna M. Brígido-Corachán IULMA - Universitat de València, Spain   ABSTRACT This article focuses on two non-fiction works by Native American author N. Scott Momaday: his 1969 historical memoir The Way to Rainy Mountain and his essay collection The Man Made of Words It specifically tackles performative conceptions of language in the Kiowa storytelling tradition, where words are experienced as speech acts that have the power to intervene in surrounding realities. Taking into account 20th century ethno-cultural and linguistic policies in the United States, the article also reflects on the role indigenous languages may play in contemporary Native American Literature, which has most often been written in English.